The nutritional status of zinc in children and adolescents with down syndrome: Child development under discussion - Delambert , Cristina Helena de Lima; Santos , Ingrid da Silva; Moreira , Bruno Zanluqui; Hashimoto , Miriam; Prearo , Alice Yamashita; Carvalho , Lidia Raquel de; Fonseca , Catia Regina Branco da (Seven Editora, 2023)
Down Syndrome (DS) is a chromosomal disorder. Studies have sought the mechanisms involved in the pathophysiology of diseases associated with DS, as well as the factors that contribute to changes growth and development. Thyroid dysfunctions as well as micronutrient deficiencies have already been evidenced. Zinc is one of the micronutrients involved in the processes of cell differentiation, height growth, neurological development and immune defense, and its deficiency can lead to damage in children with DS. There are no studies in Brazil and the real magnitude of this deficiency is not known in the general population and more specifically among those with DS. The objective of this study was to evaluate the nutritional status of zinc in children and adolescents with and to verify the response to supplementation of this micronutrient, proposing an assistance protocol for this population. A case-control clinical study and a randomized clinical trial, accomplished in 2020 and 2021, in an outpatient service of a University Hospital, with a convenience sample. Case Group: children and adolescents with DS, paired by sex and age with the control group, without the syndrome (1:1), wirh the laboratory analysis of erythrocyte and serum zinc dosages, in addition to assessment of dietary zinc intake. Study approved by the Research Ethics Committee. The results shows differences between groups were significant in relation to birth weight (p=0.04), and regarding the level of erythrocyte zinc (p<0.001), lower in the control group, despite the fact that the diet of both groups did not show insufficiency in the consumption of this micronutrient. We considerer that with the improvement of care for these children and adolescents will promote better growth and development, impacting their quality of life and that of their caregivers. In opposition to what is described in the literature, children and adolescents with Down syndrome presented better adequacy of the nutritional status of zinc than the control group. The results highlight the relevance of regular follow-up in a health care service, with integral care and multidisciplinary team, from the first months of life. DOI:https://doi.org/10.56238/alookdevelopv1-131